Outcome and clinical features in juvenile myasthenia gravis: A systematic review and meta-analysis - Lin, Yangtao; Kuang, Qianjin; Li, Hongjin; Liang, Bo; Lu, Jiaxin; Jiang, Qilong; Yang, Xiaojun (Frontiers in Neurology, 2023)
Background Juvenile myasthenia gravis (JMG) is a rare autoimmune disease that has so far only been described in small cohort studies. We defined the clinical characteristics, management, and outcomes of JMG patients over the past 22 years. Methods A search of PubMed, EMBASE, and web of science (1/2000–2/2022) identified all English language and human studies of JMG. The population was patients diagnosed with JMG. Outcomes included the history of myasthenic crisis, autoimmune comorbidity, mortality, and treatment outcome. Data extraction was performed by independent reviewers. And we performed a pooled reanalysis of all published data in the included studies and compared with other studies of adult cohorts. Results We identified 11 articles describing 1,109 patients diagnosed between 2006 and 2021. JMG occurred in 60.4% of female patients. The mean age at presentation was 7.38 years old, and 60.6% of the patients had ocular symptoms as the first clinical manifestation. The most common initial presentation was ptosis, which occurred in 77.7% patients. AchR-Ab positive accounted for 78.7%. 641 patients received thymus examination, found to have thymic hyperplasia in 64.9% and thymoma in 2.2%. Autoimmune comorbidity was found in 13.6% and the most common one is thyroid disease (61.5%). First-line therapy, including pyridostigmine and steroids, was initiated in 97.8 and 68.6%, respectively. Six patients resolved spontaneously without treatment. Thymectomy was performed in 45.6%. 10.6% of patients had a history of myasthenic crisis. Completely stable remission was achieved in 23.7% and mortality was reported in 2 studies, which reported 8 deaths. Conclusion JMG is a rare disease with a relatively benign course, and differs from adult MG in some clinical features. The treatment regimen guideline for children is still not well-established. There is a need for prospective studies to properly evaluate treatment regimes.